Proportion of dry eye in type II diabetics - Gagandeep K. Brar; Maninder Bawa; Charu Chadha; Twinkle Gupta; Harnoor Kaur (Journal of Family Medicine and Primary Care, 2024)
Introduction: Diabetes mellitus is a multisystem disorder, which is one of the most prevalent and important non-infectious causes of morbidity and mortality worldwide. While diabetic retinopathy (DR) and diabetic cataracts are well-known complications, dry eye syndrome (DES), also referred to as keratoconjunctivitis sicca, is also common in the diabetic population. If left untreated, severe dry eye may lead to eye inflammation, abrasion of the corneal surface, corneal ulcers, and vision loss. So, it is very important to diagnose it earlier as these devastating complications can be prevented. Materials and Methods: A total of 200 adult patients diagnosed with type II diabetes of either sex with an age more than 40 years were selected. Complete ophthalmological examination was done. Dry eye was diagnosed on the basis of various objective tests, and proportion of dry eye and its relation with glycemic control were studied. Conclusion: Patients with uncontrolled type II diabetes had a higher proportion of dry eye disease. A significant co-relation was found among the FBS levels, the HbA1c levels, age, duration of disease, and dry eye in patients with diabetes. No significant co-relation was found between the sex of the patient and dry eye in patients with diabetes. Hence, our study recommends that primary care physicians should advise their patients to get clinical evaluation for dry eye done along with diabetic retinopathy in uncontrolled diabetes.